Perbaikan Kuat Geser Pasir Bergradasi Buruk dengan Penambahan Abu Cangkang - Yusti Yudiawati; Muhammad Syawaluddin (Fakultas Teknik, 2023)
Based soil that does not meet technical requirements is a problem for construction executant in South Kalimantan. One of them is loose sand soil. Stabilization is carried out to improve the physical and mechanical properties of loose sand using palm shell ash waste. Sand samples were released from Bangkal village, Cempaka District, Banjarbaru. The study was conducted by adding palm shell ash to mixed variations of 0%, 5%, 10%, and 15%, to the weight of soil samples. And carried out physical and mechanical tests of the soil in the original condition and which was given a mixture of palm shell ash. The test resulted degradation in the specific gravity of the soil from 2.61 to 2.59 in 5% mixture, 2.58 in 10% mixture, and 2.56 in 15% mixture, the optimum moisture content from 15.46% to 2.08%, and the cohesion value from 0.107 kg/cm2 to 0.042 kg/cm2. It results an increase in dry fill weight from 1.47 gr/cm3 to 1.55 gr/cm3 and a shear angle value in the soil from 35.79° to 45.06°. The mixture of 15% is the optimal addition of palm shell ash that increases the shear strength of the soil.